Bureaucratic Ethics and Organizational Integrity: The Challenges of Anti-Corruption Culture in Apparatus Behavior - Ampauleng Ampauleng; Salma Abdullah; Achmad Amzal Maulana (Universitas Pancasakti, 2026)
This study examines the dynamics of bureaucratic ethics and organizational integrity as the foundation of apparatus behavior in facing the challenges of anti-corruption culture. The main focus of this study is to analyze how ethical values are internalized in organizational behavior in order to minimize corrupt practices in the public sector. The main problem raised is the disconnect between formal anti-corruption regulations and the reality of apparatus behavior that is still shackled by bureaucratic pathologies and personal loyalty. The research method used is library research with a descriptive qualitative approach. The analysis is carried out by synthesizing various academic literature, organizational behavior theories, and related policy documents to map contemporary challenges in the development of integrity in the government environment. The results of the study show that organizational integrity is highly dependent on the strength of individual ethics and the work climate that supports transparency. The biggest challenge in building an anti-corruption culture comes from political pressure and permissive organizational culture. This study concludes that strengthening anti-corruption behavior requires more than just systemic supervision, but rather the reconstruction of organizational culture that prioritizes the moral independence of the apparatus. Theoretically, this article enriches the discourse of Government Science regarding corruption prevention strategies through behavioral approaches.